Eruptive Massive Vector Particles of 5-Dimensional Kerr-Godel Spacetime - Övgün, Ali; Sakalli, I. (Springer/Plenum Publishers, 2018)
In this paper, we investigate Hawking radiation of massive spin-1 particles from 5-dimensional Kerr-Godel spacetime. By applying the WKB approximation and the Hamilton-Jacobi ansatz to the relativistic Proca equation, we obtain the quantum tunneling rate of the massive vector particles. Using the obtained tunneling rate, we show how one impeccably computes the Hawking temperature of the 5-dimensional Kerr-Godel spacetime.
Keywords: Hawking radiation; Vector particles; Quantum tunneling; Kerr-Godel spacetime